E-GOVERNMENT AND THE RELEVANCE OF THE 2014 FISCAL PROVISION RELATIVE TO THE ELECTRONIC PAYROLL RECEIPT - Esparza, Martha Luisa Puente; Facundo, Maria del Socorro Marina Ortiz; Quintero, Gloria Eneida Becerra (European Scientific Journal, ESJ, 2014)
Internationally, the complexity of the Mexican tax laws is recognized. Also, the tax authority emphasizes the need for people to acquire the fiscal culture because of the low level of tax takings; in their opinion, to the perception taxpayers in particular and society in general have about the fate of the takings, generating a high evasion rate. According to data from the Global Competitiveness Report 2010-2011, of the World Economic Forum, Mexico should strengthen its internal technological structure in order to address the factors that adversely affect their development. Some of these factors are the inefficiency of public institutions, excessive regulation and lack of an enabling environment for the adoption of new technologies. (Parliamentary Gazette, 2011) Notwithstanding the above and trying to increase revenue, minimize tax evasion and ensure that taxpayers meet their obligations, Mexican government implemented several provisions to be electronically fulfilled. One is; obligation starting from 2014 as regards employers and employees on the electronic payroll receipt, which represents difficulties for the considerable number of subordinate employees that have poor academic preparation and low income according to statistics from INEGI. Nowadays, they should have computer equipment to receive electronic files (pdf, xml); and also, must be able to handle that computer equipment and know how to save the appropriate files to comply with the provisions that came into force in 2014. The main purpose is to establish whether workers have the infrastructure and expertise for the management of electronic files, and the cost this will represent them to comply with the new provision, taking into account the principle of neutrality contained in the Federal Government Law. To achieve the objective, a sample criterion for large populations was set and applied in the city of San Luis Potosi, establishing the percentage of workers and employees, who are unaware of the new requirement, lack of the equipment, Internet service, e-mail address and have not been informed by their employers.